PERAN BUDAYA JAWA DALAM PEMBENTUKAN KARAKTER DAN KEPRIBADIAN ANAK - Amin, Muhammad Nurois (Ngabari: Jurnal Studi Islam dan Sosial, 2018)
This study aims to determine the role of Javanese culture in the formation of children's character and personality. Character is a term that refers to the application of good values ??in the form of behavior. Which includes Javanese culture is Javanese language and literature. Moral values ??contained in Javanese language and literature are manifestations of Javanese values, such as norms, beliefs, habits, conceptions, and symbols that live and develop in Javanese society, tolerance, compassion, mutual cooperation, andhap asor, humanity, respect, thankfulness, and others can be used as a source of character formation. The realization of the nation's character education from the sources of Javanese language and literature can be started from the education community through learning Javanese language and literature and the development of school culture. In learning Javanese language and literature, it should be able to take place through the process of meaning making,) so that there will be internalization of values ??in the child. The development of a community culture can be done by giving exemplary directly in accordance with the cultural values ??of Javanese language and literature.